2002
DOI: 10.1074/jbc.m109919200
|View full text |Cite
|
Sign up to set email alerts
|

The Xenograft Antigen Bound to Griffonia simplicifolia Lectin 1-B4

Abstract: The shortage of organs for transplantation into human patients continues to be a driving force behind research into the use of tissues from non-human donors, particularly pig. The primary barrier to such xenotransplantation is the reaction between natural antibodies present in humans and Old World monkeys and the Gal␣(1-3)Gal epitope (xenograft antigen, xenoantigen) found on the cell surfaces of the donor organ. This hyperacute immune response leads ultimately to graft rejection. Because of its high specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 40 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…On these grounds, the blood group Bspecific Griffonia simplicifolia I-B 4 isolectin is perhaps more appropriate for comparison (7). A recent x-ray crystallographic structural analysis of G. simplicifolia I-B 4 isolectin complexed with Gal␣1,3Gal revealed that its binding pocket is restricted to the terminal nonreducing sugar, consistent with data showing the lectin to have similar affinity for monosaccharide and the various positional isomers of the disaccharide (8). However, MOA is expected to have an extended binding site to explain its overwhelming preference for Gal␣1,3Gal-containing di-and trisaccharides.…”
supporting
confidence: 51%
“…On these grounds, the blood group Bspecific Griffonia simplicifolia I-B 4 isolectin is perhaps more appropriate for comparison (7). A recent x-ray crystallographic structural analysis of G. simplicifolia I-B 4 isolectin complexed with Gal␣1,3Gal revealed that its binding pocket is restricted to the terminal nonreducing sugar, consistent with data showing the lectin to have similar affinity for monosaccharide and the various positional isomers of the disaccharide (8). However, MOA is expected to have an extended binding site to explain its overwhelming preference for Gal␣1,3Gal-containing di-and trisaccharides.…”
supporting
confidence: 51%
“…the ␣-D-galactosyl group) (27,28). This concept of a restricted site was substantially verified by the recently completed x-ray crystallographic structure of the B 4 isolectin complexed with Gal␣1,3Gal in which it is shown that only the nonreducing ␣-galactosyl group makes contact with the lectin (29). Moreover, Kirkeby and Moe (30), using an enzyme-linked lectin assay, showed that the ␣-galactosyl group and the ␣1,2-, ␣1,3-, and ␣1,4-galactobiosyl groups as well as the linear B-trisaccharide (Gal␣1,3Gal␤1,4GlcNAc) linked to human serum albumin were very similar in their binding affinity to GS I-B 4 .…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, both galactose units are relatively tightly bound compared with the GlcNAc unit at the reducing end of the sugar. In contrast, the Griffonia simplicifolia isolectin GS I-B4 forms a deep pocket favoring the recognition of terminal galactose and thus broader specificity (60). The fact that the MOA accepts the fucosylated blood group antigen B, whereas the M86 antibody does not, is the best evidence for their different binding pocket structures.…”
Section: Discussionmentioning
confidence: 91%